2014
DOI: 10.1073/pnas.1324201111
|View full text |Cite
|
Sign up to set email alerts
|

Conformational change in the periplamic region of the flagellar stator coupled with the assembly around the rotor

Abstract: The torque of the bacterial flagellum is generated by the rotorstator interaction coupled with the ion flow through the channel in the stator. Anchoring the stator unit to the peptidoglycan layer with proper orientation around the rotor is believed to be essential for smooth rotation of the flagellar motor. The stator unit of the sodium-driven flagellar motor of Vibrio is composed of PomA and PomB, and is thought to be fixed to the peptidoglycan layer and the T-ring by the C-terminal periplasmic region of PomB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 36 publications
6
111
0
Order By: Relevance
“…For V. fischeri, these proposed stator complexes were consistent with the size of a recent single-particle reconstruction of the Vibrio stator complex (16). The densities spanned the C-ring to ∼10 nm above the inner membrane, as previously predicted (34), were arranged in a 17-nm radius ring with a with 13-fold rotational symmetry, and contacted the 16-nm radius T-ring ( Fig. 2 A-D, red arrows; continuous density is best visualized in Fig.…”
Section: Three Flagellar Motors That Produce Different Torques Are Stsupporting
confidence: 88%
“…For V. fischeri, these proposed stator complexes were consistent with the size of a recent single-particle reconstruction of the Vibrio stator complex (16). The densities spanned the C-ring to ∼10 nm above the inner membrane, as previously predicted (34), were arranged in a 17-nm radius ring with a with 13-fold rotational symmetry, and contacted the 16-nm radius T-ring ( Fig. 2 A-D, red arrows; continuous density is best visualized in Fig.…”
Section: Three Flagellar Motors That Produce Different Torques Are Stsupporting
confidence: 88%
“…Considering the torque produced by N stators as Nτ 1 = γ2πω N (where τ 1 is the torque produced by a single stator, γ the drag coefficient of the bead, and ω N the measured speed (in Hz) of the motor with N stators), all the strains tested are driven by N ~ 8-10 stators, in line with previous measurements at high load 15,44 . This result supports previous works focused on quantifying steady-state stator stoichiometry by fluorescent stators 15,[18][19][20][21]28,29,[45][46][47] .…”
Section: Resultssupporting
confidence: 91%
“…It has been suggested that force upon the PG may cause structural changes in stator binding sites which may affect stator unit association rate (17). Additionally, crystal structures of MotBC of Salmonella and PomBC of Vibrio suggest that a drastic conformational change in the N-terminal portion of MotBC /PomBC is required for the stator to bind to the PG (38,39). Mutational studies suggest that this conformational change may be triggered by an interaction between the cytoplasmic domain of MotA and FliG (40), a process potentially complicated by the rotation of the rotor.…”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly, it has been reported that the putative key PGB residues in the structure of the PGB dimer of MotB are buried and not readily accessible (44) and that a substantial structural flexibility of the domain is considered necessary to mask and unmask them (45). The Nterminal portion of MotB must perform a large conformational extension to reach the PG (38,39). Recently, a conformational change upon binding has also been hypothesized in the PGassociated C-terminal of the closely related Outer Membrane protein OmpA (46).…”
Section: Discussionmentioning
confidence: 99%